Ave Maria - William, Andrea Flavia (2018)
Ave Maria is a tamil art film produced by 3.1 Productions, as part as an undergraduate Final Year Project (FYP) in the Wee Kim Wee School of Communication and Information (WKWSCI), Nanyang Technological University (NTU). It is created by Andrea Flavia William, Ang Cai Wen, Corin Too Jia Hui and Kuang Zi Ling under the supervision of Mr. Daniel Heng. This report provides a detailed account from conceptualisation to post-production and seeks to address the motivations and creative decisions that were taken in order to create this film. It also highlights the obstacles faced and solutions taken to overcome it.